Safety of EUS-guided gallbladder drainage using a lumen-apposing metal stent in patients requiring anticoagulation - Catherine Frakes Vozzo, DO; C. Roberto Simons-Linares, MD; Mohannad Abou Saleh, MD; Tyler Stevens, MD; Prabhleen Chahal, MD (VideoGIE, 2020)
Background and Aims: EUS-guided gallbladder drainage (EUS-GBD) can be used to treat acute cholecystitis in patients with medical comorbidities that prevent definitive operative management. Historically, nonsurgical management of cholecystitis was achieved by way of percutaneous gallbladder drainage. Methods: We examined the periprocedural bleeding rate of EUS-GBD for acute cholecystitis using lumen-apposing metal stents in 5 high-surgical-risk patients requiring anticoagulation. Data on 5 nonoperative candidates with acute cholecystitis who underwent EUS-GBD were studied retrospectively. Results: There were no immediate or delayed postprocedure adverse events, including bleeding. Conclusions: Although further study is needed, EUS-GBD appears safe in patients who require periprocedural anticoagulation.